An Assessment of the economic and social impacts of climate change on the health sector in the Caribbean - Clarke, Christine [et al] (UN New YorkUS, 2013)
Aims to prepare the Caribbean to respond better to the anticipated impact of climate change on the health sector, while fostering a subregional Caribbean approach to reducing carbon emissions by 2050. Provides a major advance on the analytical and contextual issues surrounding the impact of climate change on health in the Caribbean by focusing on the vector-borne and waterborne diseases that are anticipated to be impacted directly by climate change.